A review of low-rank coals liquefaction processes containing water and syngas (or CO). (15th January 2023) - Li, Huan; Peng, Wencai; Zhu, Di; Gu, Jiale; Wu, Youqing; Huang, Sheng; Gao, Jinsheng; Zhao, Baofeng; Guan, Haibin; Li, Chao; Xu, Jing; Bai, Jinfeng; et al.
Highlights: DCLS is an effective method that can convert low-rank coals into fuels. The effects of coal, catalyst, and solvent on liquefaction behaviors are summarized. The coal liquefaction mechanisms (especially WGSR mechanisms) in DCLS are reviewed. The potential challenges for the development and application of DCLS are discussed. Abstract: With the increasing demand for energy and raw materials, the importance of effective utilization of low-rank coals has been emphasized. The utilization of low-rank coals in direct liquefaction is limited by their high oxygen and moisture contents because large amounts of hydrogen and energy are required for oxygen removal and drying, respectively. Direct coal liquefaction in the system containing water and syngas or CO (DCLS) is an economical and effective method that can convert low-rank coals into fuels and value-added chemicals in the conditions of no pure hydrogen (or hydrogen-poor gas) and drying, thus resulting in the whole cost reduction for the utilization of DCLS. This review presents the latest development of DCLS, focusing on critical liquefaction behaviors (mainly the effects of various parameters such as coals, catalysts, solvents, as well as appropriate reaction temperatures and pressures on the liquefaction behaviors), widely recognized catalytic liquefaction mechanisms (especially water–gas shift reaction), and liquefaction technological processes. On the basis of the above inductions, analyses and discussions, the potential opportunities and challenges for the development and application of DCLS are emphasized. This review aims at discussing valuable technologies to provide more solutions for the efficient utilization of low-rank coals.